Group-based compassion-focused therapy for prolonged grief symptoms in adults – Results from a randomized controlled trial - Johannsen, Maja; Schlander, Christina; Farver-Vestergaard, Ingeborg; Lundorff, Marie; Wellnitz, Kaare Bro; Komischke-Konnerup, Katrine B.; O'Connor, Maja (Psychiatry research, 2022)
•Group-based Compassion-Focused Therapy (CFT) is not efficacious for reducing prolonged grief symptoms (PGS) in adults.•CFT may not adequately target core maintaining processes in pathological grief.•CFT delivered in groups may be a less than optimal delivery format and eight sessions may be too few to facilitate positive change.•Given the design of the present study, the efficacy of individual CFT components remains unclear. Prolonged grief disorder is a debilitating condition, which affects approximately one out of ten who lose a loved one. While existing meta-analyses have synthesized evidence regarding the overall effect of psychological interventions for pathological grief across different types of psychotherapy, it remains clinically relevant to explore whether specific types of psychological interventions are efficacious in the treatment of grief. The present study investigated the efficacy of group-based Compassion-Focused Therapy (CFT) for adults who had lost a spouse or a parent, and who reported clinically relevant levels of prolonged grief symptoms (PGS) at 11 months post-loss. A total of 82 participants were randomized to the CFT group (n = 42) or the waitlist control (n = 40). Time × group interactions showed no statistically significant effects of the intervention on the primary outcome PGS at post-intervention or 6-month follow-up. Likewise, no statistically significant effects were found for any of the secondary outcomes or process variables, with the exception of posttraumatic stress symptoms and self-reassurance. Taken together, in the present study group-based CFT did not emerge as an efficacious treatment for PGS. Possible explanations include that CFT may not target core maintaining processes in PGS and that the group-based, 8-week operationalization of CFT may be less than optimal.